2012
DOI: 10.1128/aem.00555-12
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Two-Component System CBO0366/CBO0365 in the Cold Shock Response and Growth of Group I (Proteolytic) Clostridium botulinum ATCC 3502 at Low Temperatures

Abstract: bThe role of the two-component system (TCS) CBO0366/CBO0365 in the cold shock response and growth of the mesophilic Clostridium botulinum ATCC 3502 at 15°C was demonstrated by induced expression of the TCS genes upon cold shock and impaired growth of the TCS mutants at 15°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…TCSs responding to low temperature on the transcriptional level have been reported in group I C. botulinum organisms (27,28). Similar to the current study, the previous works showed that the relative expression levels of cbo0366/cbo0365 and cbo2306/cbo2307 in group I C. botulinum organisms was most increased 5 h after the cold shock when calibrating the cold-shocked culture to the nonshocked culture.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…TCSs responding to low temperature on the transcriptional level have been reported in group I C. botulinum organisms (27,28). Similar to the current study, the previous works showed that the relative expression levels of cbo0366/cbo0365 and cbo2306/cbo2307 in group I C. botulinum organisms was most increased 5 h after the cold shock when calibrating the cold-shocked culture to the nonshocked culture.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, all of the mutants grew less efficiently than the WT at 12°C, and this finding was further confirmed by successful complementation of the mutations. Loss of growth efficiency at low temperature (15°C) was also reported for the group I C. botulinum TCS mutants with mutations of cbo0366, cbo0365, cbo2306, and cbo2307 (27,28), which affirms the general role of TCSs in the cold tolerance of C. botulinum. A protein blast analysis suggests that neither CBO0366/CBO0365 nor CBO2306/CBO2307 is the closest homologue to CLO3403/CLO3404.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The C. botulinum ATCC 3502 wild-type strain was evaluated for relative sigK expression levels after cold shock, exposure to hyperosmotic conditions, exposure to acidity, or under optimal growth conditions, using quantitative reverse transcription-PCR (primers sigK-qPCR-F [5=-ACTTATGGGATGTACTAGGAAGT G-3=] and sigK-qPCR-R [5=-TTCTTCTTCATCACTTAGAGGCT TG-3=]) (17)(18)(19) and the Pfaffl method (20) for quantitation, with 16S rrn expression as a normalization reference (primers 16Srrn-qPCR-F [5=-AGCGGTGAAATGCGTAGAGA-3=] and 16Srrn-qPCR-R [5=-GGCACAGGGGGAGTTGATAC-3=]). In temperature downshift, cultures grown to the early logarithmic phase at 37°C were rapidly cooled to 15°C and thereafter anaerobically incubated at 15°C for 5 h. The actual temperature of the cultures varied between 14 and 18°C.…”
mentioning
confidence: 99%
“…Insertional inactivation mutants of sigK with the ClosTron insertion (22,23) in a sense (sigK-427s) or antisense (sigK-296as) orientation (12) were evaluated for their growth characteristics at 17 and 37°C under hyperosmotic conditions (4.5% [wt/vol] NaCl) and at pH 6.0, 5.3, and 5.0 (17)(18)(19)24). The growth rate and maximum optical density of the wild-type strain at 17°C were significantly higher than those of the sigK-427s and sigK-298as mutants (Fig.…”
mentioning
confidence: 99%